Ancient plants with ancient fungi: liverworts associate with early-diverging arbuscular mycorrhizal fungi. Issue 1888 (10th October 2018) - Rimington, William R.; Pressel, Silvia; Duckett, Jeffrey G.; Field, Katie J.; Read, David J.; Bidartondo, Martin I.
Abstract : Arbuscular mycorrhizas are widespread in land plants including liverworts, some of the closest living relatives of the first plants to colonize land 500 million years ago (MYA). Previous investigations reported near-exclusive colonization of liverworts by the most recently evolved arbuscular mycorrhizal fungi, the Glomeraceae, indicating a recent acquisition from flowering plants at odds with the widely held notion that arbuscular mycorrhizal-like associations in liverworts represent the ancestral symbiotic condition in land plants. We performed an analysis of symbiotic fungi in 674 globally collected liverworts using molecular phylogenetics and electron microscopy. Here, we show every order of arbuscular mycorrhizal fungi colonizes early-diverging liverworts, with non-Glomeraceae being at least 10 times more common than in flowering plants. Arbuscular mycorrhizal fungi in liverworts and other ancient plant lineages (hornworts, lycopods, and ferns) were delimited into 58 taxa and 36 singletons, of which at least 43 are novel and specific to liverworts. The discovery that early plant lineages are colonized by early-diverging fungi supports the hypothesis that arbuscular mycorrhizas are an ancestral symbiosis for all land plants.